Administración de justicia de las rondas campesinas durante estado de emergencia por Covid-19 en el distrito de Chota-2020 - Gonzales Gonzales, Maria Nelsy (2022)
This thesis Administration of justice of the Rondas Campesinas during a state of emergency by Covid-19 in the district of Chota-2020, has been carried out with the objective of analyzing and describing the administration of justice of the Rondas Campesinas during the state of emergency by Covid-19 through social control, analysis and description of the Justice Administration of the Rondas Campesinas, analysis and description of Social Control in the different streets of the district, main access roads to the district and; in markets and shopping malls during the state of emergency. A qualitative methodological approach is used. There is a sample of thirty ronderos applying the ethnographic method, the historical method, the phenomenological method and the inductive method, as well as the techniques of direct observation, bibliographic review, semi-structured interview and life history, likewise, instruments were used. such as field notebook, interview guide, digital camera and audio recorder. It is concluded that the Rondas Campesinas can exercise authority in situations of health emergency just like state authorities of the Government, they administer justice based on the Law of Rondas Campesinas Nº27908 and the Political Constitution of Peru, a justice of uses and customs that is governed by the dialogue, prevention and awareness, but also applies physical and moral sanctions.